Follow-up of at least 3 years after ganglion impar block for control of chronic coccygodynia - GÜNDÜZ, OSMAN HAKAN; OKÇU, MEHMET (My University, 2023)
IntroductionAlthough it is well known that ganglion impar block (GIB) reduces pain in the short term in patients with chronic coccygodynia, there are insufficient data on long-term treatment outcomes. The aim of this study was to examine the long-term outcomes of patients who underwent GIB for chronic coccygodynia and possible factors that might affect these outcomes.MethodsThe pre-treatment, 1st-hour, and 3rd-week numeric rating scale (NRS) scores of patients who underwent GIB 36-119 (min-max) months ago (between November 2011 and October 2018) due to coccygodynia were obtained from the medical records. Final NRS scores and presence of factors that may affect success such as accompanying low back pain (LBP) were questioned via telephone interviews. Treatment success was defined as a 50% or more reduction in final NRS scores compared with pre-treatment NRS scores.ResultsTelephone interviews were made with 70 patients. Treatment success was achieved in 55.7% of the patients. The patients were divided into two groups as those who achieved treatment success (group A) and those who could not (group B) and were compared. The NRS scores at the 3rd week and the number of patients with LBP in the group B were significantly higher than the group A. No serious complications developed in any patients.ConclusionIn patients with chronic coccygodynia, GIB is an effective and safe treatment option for pain reduction in the long term. Accompanying LBP and high pain scores in the 3rd week after injection should be considered as parameters that negatively affect long-term treatment success.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; SİNİR BİLİMİ; Sinirbilim ve Davranış; Yaşam Bilimleri (LIFE); NEUROSCIENCES; NEUROSCIENCE & BEHAVIOR; Life Sciences (LIFE); Duyusal Sistemler; Gelişimsel Sinirbilim; Bilişsel Sinirbilim; Hücresel ve Moleküler Sinirbilim; Sinirbilim (çeşitli); Genel Sinirbilim; İnsan Bilgisayar Etkileşimi; Fizik Bilimleri; Sensory Systems; Developmental Neuroscience; Cognitive Neuroscience; Cellular and Molecular Neuroscience; Neuroscience (miscellaneous); General Neuroscience; Human-Computer Interaction; Physical Sciences; Coccygodynia; ganglion impar; ganglion impar block; long-term outcomes; long-term follow-up; CHRONIC COCCYDYNIA; PAIN; TRANSSACROCOCCYGEAL; Coccygodynia; ganglion impar; ganglion impar block; long-term outcomes; long-term follow-up